2009
DOI: 10.1136/tc.2009.030759
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of tobacco use among the Iranian adult population: results of the national Survey of Risk Factors of Non-Communicable Diseases (SuRFNCD-2007)

Abstract: BackgroundPrevious studies report on smoking in Iran but recent national data on tobacco use (including cigarette, water-pipe and pipe) have not been reported.MethodsIn 2007, 5287 Iranians aged 15–64 years were sampled from all provinces as part of a national cross-sectional survey of non-communicable disease (NCD) risk factors. Data were collected using the standardised stepwise protocol for NCD risk factor surveillance of the World Health Organization. Use of tobacco products was calculated as the sum of smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
115
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(141 citation statements)
references
References 5 publications
18
115
6
Order By: Relevance
“…The result of our study showed that the prevalence of cigarette smoking was about 9% in Birjand, Iran. The prevalence of cigarette smoking was lower than similar studies from Iran (8,14,15). Although, Kazemi et al indicated that smoking prevalence was 3.9% between nurses in Birjand, east of Iran (16).…”
Section: Discussioncontrasting
confidence: 47%
“…The result of our study showed that the prevalence of cigarette smoking was about 9% in Birjand, Iran. The prevalence of cigarette smoking was lower than similar studies from Iran (8,14,15). Although, Kazemi et al indicated that smoking prevalence was 3.9% between nurses in Birjand, east of Iran (16).…”
Section: Discussioncontrasting
confidence: 47%
“…It is estimated that there are about 4 million death due to smoking in the world and it is going to rise to 8.4 million death per year by 2020, and 66% of them will be in developing countries [20]. In our study prevalence of smoking was 11.9% (10.1% men vs. 1.8% women) which in comparison to results of national survey of non communicable disease in Iran (14.8% overall, 26.1% men, 3.2% women) is lower because we categorized people who had smoked water pipe in a different group [21]. In Uromia (a province in North West of Iran), prevalence of smoking was 3.6% in women and 30.5% in men [22].…”
Section: Discussionmentioning
confidence: 64%
“…However according to national survey of non communicable disease in Iran; water pipe is the most form of tobacco use in Iranian women and they may not use it regularly but in many occasions [21]. As it shown in Table 3 water pipe smoking has a significant relationship with "wheezing", which may alert us about upcoming asthma symptoms in water pipe smokers in next few years.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of 235 hookah users, 58.3% believed that hookah was less harmful than cigarette smoking (7)(8)(9). It has been shown that in a single hookah smoking session (typically 15 g of tobacco for 45 minutes), smokers were exposed to three to nine times more carbon monoxide (CO) and 1.7 times more nicotine in comparison to cigarette smoking.…”
Section: Is the Hookah Inhaling Smoke Less Harmful Than Cigarette Smomentioning
confidence: 99%